If the shoe fits - Bell, Krista; Smith, Craig, 1955- (Watertown, MA : Charlesbridge, 2008)
Cassie wants to be a dancer when she grows up but is afraid to dance in front of anyone outside her family, until the day of her first jazz performance arrives and her mother and a new friend help her to gain confidence.
K
b
b
Keywords: Self-confidence -- Fiction; Jazz dance -- Fiction; Dance recitals -- Fiction; Dance -- Fiction; Friendship -- Fiction